2020
DOI: 10.3389/fendo.2020.00612
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Vertebral Body Segmentation Based on Deep Learning of Dixon Images for Bone Marrow Fat Fraction Quantification

Abstract: Background: Bone marrow fat (BMF) fraction quantification in vertebral bodies is used as a novel imaging biomarker to assess and characterize chronic lower back pain. However, manual segmentation of vertebral bodies is time consuming and laborious. Purpose: ( 1 ) Develop a deep learning pipeline for segmentation of vertebral bodies using quantitative water-fat MRI. ( 2 ) Compare BMF measurements between manual and automatic segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Another similar results was from the study of automatic vertebral body segmentation that based on deep learning of Dixon images with an AUC of 0.92 and a mean Dice coefficient of 0.849±0.091 (10). These parameter values suggest that solely using BMFF average and demographic characteristics is not as effective as using radiomic models.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Another similar results was from the study of automatic vertebral body segmentation that based on deep learning of Dixon images with an AUC of 0.92 and a mean Dice coefficient of 0.849±0.091 (10). These parameter values suggest that solely using BMFF average and demographic characteristics is not as effective as using radiomic models.…”
Section: Discussionsupporting
confidence: 53%
“…Rastegar et al (9) developed classification models to predict osteoporosis and osteopenia using radiomics on bone mineral densitometry images, achieving arear under the receiver operator characteristic curve (AUC) values from 0.50 to 0.78. Zhou et al found that deep learning can provide automated segmentation of vertebral bodies using water-fat MR (Dixon) images to qualify bone marrow fat recently (10). However, there is no study to for ABD and osteoporosis prediction, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has been exploring the use of deep learning-based AI systems which are able to perform multiple tasks at the basic and advanced level in a single model [1]. Vertebrae are by far the most investigated structure, with AI systems reaching > 90% DICE and > 90% accuracy in the majority of studies included in our review, both using DIP [28][29][30][31][32][33][34][35][36][37][38][39][40][41]43,44,[48][49][50]53,61,62] and deep learning models [67,69,77,[80][81][82][83][84]. In particular, a study from Lee et al [40] proposed a model to obtain an automated segmentation of lumbar pedicles from CT images in order to increase accuracy and safety during transpedicular screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they used a deformed U-net [76] for the segmentation of paraspinal muscles on 120 MRI achieving an overall DICE greater than 91.3%. Zhou et al [77] utilized a U-net for vertebrae segmentation on MRI of 57 subjects, achieving a DICE of 84.9%.…”
Section: Deep Learningmentioning
confidence: 99%
“…One strength of our study is the deployment of two recently developed neural networks [15,16] to perform automated tissue segmentation. This enabled rapid and unbiased evaluation of the MRI biomarkers, demonstrating the relevance of neural networks to a diverse class of problems and addressing the inefficiency and subjectivity associated with manual tissue segmentation.…”
Section: Discussionmentioning
confidence: 99%